2005
DOI: 10.1029/157gm12
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel inversion of scattered teleseismic body waves: Practical considerations and applicability

Abstract: We investigate the resolving power and applicability of a recently developed technique for multichannel inversion of scattered teleseismic body waves recorded at dense seismic arrays. The problem is posed for forward-and back-scattered wavefields generated at discontinuities in a 2D isotropic medium, with the backprojection operator cast as a generalized Radon transform (GRT). The approach allows for the treatment of incident plane waves from arbitrary backazimuths, and recovers estimates of material property … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(110 citation statements)
references
References 44 publications
1
108
1
Order By: Relevance
“…4a, the candidate phase assemblages which explain our deeper-depth ( 4 $ 100 km) data are gabbro ( $ 024% porosity) and eclogite ( $ 6% porosity). Observed dominant gabbroic phase at deeper depth ( 4 $ 100 km) is supported by the seismic image showing the sharp boundary between the top interface of the steeply subducting slab and the peridotitic mantle, which extends down to a depth of 200 km although the image does not show the oceanic Moho (bottom of the oceanic crust) due to the low frequency range in the analysis (0.03-0.3 Hz) and resolution limit (Rondenay et al, 2005;MacKenzie et al, 2010). It is generally understood that large amount of fluid is expelled from the downgoing hydrated crust as it undergoes subduction-zone metamorphism with increasing P and T, and the degree of dehydration strongly controls the reflectivity at the top and bottom of the oceanic crust (Kawakatsu and Watada, 2007).…”
Section: Central Mexicomentioning
confidence: 77%
See 1 more Smart Citation
“…4a, the candidate phase assemblages which explain our deeper-depth ( 4 $ 100 km) data are gabbro ( $ 024% porosity) and eclogite ( $ 6% porosity). Observed dominant gabbroic phase at deeper depth ( 4 $ 100 km) is supported by the seismic image showing the sharp boundary between the top interface of the steeply subducting slab and the peridotitic mantle, which extends down to a depth of 200 km although the image does not show the oceanic Moho (bottom of the oceanic crust) due to the low frequency range in the analysis (0.03-0.3 Hz) and resolution limit (Rondenay et al, 2005;MacKenzie et al, 2010). It is generally understood that large amount of fluid is expelled from the downgoing hydrated crust as it undergoes subduction-zone metamorphism with increasing P and T, and the degree of dehydration strongly controls the reflectivity at the top and bottom of the oceanic crust (Kawakatsu and Watada, 2007).…”
Section: Central Mexicomentioning
confidence: 77%
“…The subducted Cocos plate beneath central Mexico, as imaged with both RFs and teleseismic migration (Bostock et al, 2001;Rondenay et al, 2005) Waveform from teleseismic events, as shown in Fig. 1 upper-left inset, are first filtered at 0.01-1.0 Hz and processed by the time domain deconvolution (Kikuchi and Kanamori, 1982;Ligorria and Ammon, 1999) with a Gaussian filter parameter of 4.…”
Section: Geometries Of the Subducted Cocos Oceanic Crust In Mexicomentioning
confidence: 99%
“…Multichannel preprocessing approaches rely on the assumption that the incident and scattered wavefields have distinct moveouts (arrival times vs offset), and usually comprise the following steps (e.g., Rondenay et al 2005): (1) The traces are aligned relative to the incident wavefield identified on the L/P components. (2) The incident wavefield is extracted either by stacking the aligned L/P components, or by conducting Principal Component Analysis (PCA) on the aligned L/P components and retaining the first or first few components.…”
Section: Separation Of 2-d and 3-d Scattered Signalmentioning
confidence: 99%
“…The data used (∼20% of all available traces) passed selection criteria on the basis of signal-to-noise and multichannel cross-correlation values. Source signatures are estimated through principal component analysis and removed from the data through Wiener deconvolution (27,28). With GRT, we estimate (from scattered energy) elasticity contrasts at nodes of a 3D mesh (10 km vertical, 1°lateral spacing); spatial alignment of such contrasts indicates the presence of an interface.…”
Section: -2009mentioning
confidence: 99%